Staphylococcus aureus thermonuclease NucA is a key virulence factor in septic arthritis - Ningna Li; Meghshree Vinod Deshmukh; Filiz Sahin; Nourhane Hafza; Aparna Viswanathan Ammanath; Sabrina Ehnert; Andreas Nüssler; Alexander N. R. Weber; Tao Jin; Friedrich Götz (Communications Biology)
Abstract Septic arthritis, primarily caused by Staphylococcus aureus, poses a significant risk of both mortality and morbidity due to its aggressive nature. The nuc1-encoded thermonuclease NucA of S. aureus degrades extracellular DNA/RNA, allowing the pathogen to escape neutrophil extracellular traps (NETs) and maintain the infection unabated. Here we show that in the mouse model for hematogenous septic arthritis, the Δnuc1 mutant is much less pathogenic and the severity of clinical septic arthritis is markedly reduced, including decreased weight loss, lower kidney bacterial load, reduced bone erosion, and much less IL-6 production. In vitro, S. aureus genomic DNA induces a robust TNF-α response in macrophage-like RAW 264.7 cells abrogated when the DNA is degraded by NucA. Moreover, the wild type induces high levels of TNF-α, IL-10, and IL-6 in neutrophils and osteoblast-like SAOS-2 cells, respectively. NucA exacerbates septic arthritis by increasing extracellular and intracellular survival of bacteria.